The Brief Review on the Network Theory in the Electrical field (International Journal of Innovative Research in Computer Science & Technology, 2022)
Network theory investigates the operation  of diverse sectors such as commerce, electrical and  electronic circuits, and computer networks, among other  things. It has operation that is the graphical display of data  in numerous areas of activity. Network theory can graph  symmetrical and asymmetrical connections between  discrete items. In the computer science sector, for example,  network theory is defined as a graphical illustration of systems having nodes and edges. The notion of network  theory was discussed in this article, as well as its use in  numerous fields, as well as its limits and benefits. In this  post, we'll look at how network theory is used in electrical  engineering to address problems. The numbers of current  and voltage component in a circuit is first determined using  network theory, and then the circuit is simplified using  network theory. By applying complex network analysis,  this article presents a concept on complex network analysis  (CNA) as well as brief information on micro grids in electric distributions system. Network theory is learning of  electrical network that can aid in the future, such as  improving the network stability of a major power station,  increasing grid resilience, and protecting power stations  from blackouts. The study of network theory is  demonstrated in this article using MATLAB software.
Keywords: Business; Centralized; Computer; MATLAB; Network